Civil Capital, Adult Education and Community Sustainability: A Theoretical Overview - Jennifer Sumner (Adult Education Research Conference, 2000)
As communities struggle to overcome the negative impacts of corporate globalization, they are searching for ways to maintain or achieve sustainability in an era that values economic efficiency above community life and interests. Adult educators can support communities in their search for sustainability by helping to resist corporate globalization and by building civil capital.